National Education Philosophy: A Review of Its Application in Malaysia's Education System - Ismail, Noorilham; Aziz, Mohd Kasturi Nor Abd; Arsani, Zarifah; Harun, Makmur Haji (ZAHRA: Research and Tought Elementary School of Islam Journal, 2021)
The implementation of the National Education Philosophy (NEP) at each stage of learning in the Malaysian education system will be the subject of this study. The primary goal that will be stressed is the implementation of the educational philosophy at the primary, secondary, and higher education levels. The emphasis would be on the areas covered in each level of education, whether academic or co-curricular in nature. This analysis will depend on educational reports from the Malaysian Ministry of Education, as well as memoirs, books, and newspapers. Such information will be analysed, compiled, and detailed in an authoritative and insightful narrative statement. Finally, this study will demonstrate that the use of NEP in Malaysian education has been consistent since its inception and continues to this day.